(Re)interpreting Spirituality in Everyday Life – A Pastoral-Psychological Approach – - BAKK-MIKLÓSI, Kinga (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The term “spirituality” is rendered in some of the new Bible translations as “life” for good reason. Spirituality is about enlivening existence, life, the very essence of life, that which makes life into life and manifests itself in our life conduct. Spirituality goes beyond ecclesiastical religiosity, as it is in fact the “longing for a fulfilled life”. This paper aims to outline an interdisciplinary approach to the definition of spirituality while providing guidance on how to “grasp” the phenomenon in everyday life. The spiritual need of the human being is an anthropological constant, and therefore it can be suppressed but cannot be eliminated. Since the 1990s, there has been a significant[1] “religious climate change” in Europe: religiosity is currently experiencing its renaissance, with the Institute for Pastoral Sociology in Vienna noting a mega-trend in spirituality, a term that has since become widely used.[2] The subjective need for spirituality is strong in the face of, and in spite of, secularization and atheism, which has become less of a conviction and more of a habit. Thus, spirituality is the archetypal need that is present all around the world, that gives meaning to life, provides security, and helps navigating our everyday lives. In contrast to dogmatic religiosity, which is tied to denominational norms, this form is both individual and plural in its expression, in its rites, and in its morality. Its relationship to health is being studied intensively by medicine and psychology[3] and is becoming an increasingly important topic in theology.[4] At the same time, it has become part of the highest levels of economic and financial systems.[5] The church, welfare work, social work, psychotherapy, and organizational counselling[6] are forced by this revived interest to address the issue of spirituality and to draw conclusions for their own practice. In this article, we are not going to talk about this “mega-trend” but about individual, personal spirituality. We will attempt to trace the factors that shape the so-called spiritual competence. The path leads through several questions: first, why did the renaissance of spirituality happen when it did, how should we imagine spirituality, and what does it refer to? Another question is as follows: what is it that shapes our spirituality, and to what extent is it possible to find it behind the socialization that which is in us by nature? And, finally, what do the concepts of spiritual competence and spiritual care mean? [1] Houtman, Dick – Aupers, Stef (2007): The Spiritual Turn and the Decline of Tradition: The Spread of Post-Christian Spirituality in 14 Western Countries, 1981–2000. In: Journal for the Scientific Study of Religion. 46, 305–320. [2] A detailed analysis of the current situation: Zulehner, Paul M. (ed.) (2004): Spiritualität – mehr als ein Megatrend. Ostfildern. [3] They can be divided into three categories: 1) works exploring the concept of spirituality (religion), 2) research on the relationship between spirituality and health (health, patient care), and 3) comprehensive manuals and user guides to the practice of spirituality. An excellent summary of the literature: Städler, Kathrin (n. y.): Spiritualität in ihrer Bedeutung für das Gesundheits- und Sozialwesen. Eine Literaturrecherche. https://www.fh-diakonie.de/obj/Bilder_ und_Dokumente/DiakonieCare/FH-D_DiakonieCare_Staedler-K_Spiritualitaet-und-Gesundheitswiss.pdf (last accessed on: 31.10.2019). [4] While the religious studies still question whether spirituality is a relevant topic for them at all, theology has already begun to address it. E.g.: Peng-Keller, Simon (2010): Einführung in die Theologie der Spiritualität. Darmstadt; Peng-Keller, Simon (2012): Geistbestimmtes Leben: Spiritualität (Studiengang Theologie Bd. XI). Zürich; Stegemann, Wolfgang (2012): Der Heilige Geist und die Sorge um sich. Zur Einordnung der paulinischen Spiritualität. In: Schoenauer, Hermann (ed.): Spiritualität und innovative Unternehmensführung (Dynamisch Leben gestalten 3). Stuttgart. 90–107; Städler n. y.; Grom, Bernhard (2009): Spiritualität – die Karriere eines Begriffs: Eine religionspsychologische Perspektive. In: Frick, Eckhard – Roser, Traugott (eds.): Spiritualität und Medizin. Gemeinsame Sorge für den kranken Menschen. Stuttgart. 12–17. [5] Städler quotes: Baier, Karl (2006): Spiritualitätsforschung heute. In: Baier, Karl (ed.): Handbuch der Spiritualität. Zugänge, Traditionen, interreligiöse Prozesse. Darmstadt; Schoenauer, Hermann (ed.) (2012): Spiritualität und innovative Unternehmensführung (Dynamisch Leben gestalten 3). Stuttgart; Zimmerling, Peter (2010): Evangelische Spiritualität. Wurzeln und Zugänge. Göttingen; Dahlgrün, C. (2009): Christliche Spiritualität. Formen und Traditionen der Suche nach Gott. M. e. Nachwort v. L. Mödl. Berlin – New York, De Gruyter. [6] Management theory currently uses the category of “the soul of the organization”.